Aged neutrophils accumulate in lymphoid tissues from healthy elderly mice and infiltrate T‐ and B‐cell zones. Issue 8 (16th April 2018) - Tomay, Federica; Wells, Kelsi; Duong, Lelinh; Tsu, Jean Wei; Dye, Danielle E; Radley‐Crabb, Hannah G; Grounds, Miranda D; Shavlakadze, Tea; Metharom, Pat; Nelson, Delia J; Jackaman, Connie
Abstract: The average age of the human population is rising, leading to an increasing burden of age‐related diseases, including increased susceptibility to infection. However, immune function can decrease with age which could impact on processes that require a functional immune system. Aging is also characterized by chronic low‐grade inflammation which could further impact immune cell function. While changes to neutrophils in blood during aging have been described, little is known in aging lymphoid organs. This study used female C57BL/6J mice comparing bone marrow (BM), spleen and lymph nodes from young mice aged 2–3 months (equivalent to 18 human years) with healthy elderly mice aged 22–24 months (equivalent to 60–70 human years). Neutrophil proportions increased in BM and secondary lymphoid organs of elderly mice relative to their younger counterparts and presented an atypical phenotype. Interestingly, neutrophils from elderly spleen and lymph nodes were long lived (with decreased apoptosis via Annexin V staining and increased proportion of BrdU neg mature cells) with splenic neutrophils also demonstrating a hypersegmented morphology. Furthermore, splenic neutrophils of elderly mice expressed a mixed phenotype with increased expression of activation markers, CD11b and ICAM‐1, increased proinflammatory TNFα, yet increased anti‐inflammatory transforming growth factor‐beta. Elderly splenic architecture was compromised, as the marginal zone (required for clearing infections) was contracted. Moreover, neutrophils from elderly but not young mice accumulated in lymph node and splenic T‐ and B‐cell zones. Overall, the expansion of functionally compromised neutrophils could contribute to increased susceptibility to infection observed in the elderly. Abstract : In this study, we show that neutrophils increase in lymphoid organs of healthy elderly mice and infiltrate T‐ and B‐cell lymphoid areas in the absence of any pathological disease. Compared to young mice, neutrophils from elderly healthy spleens and lymph nodes expressed a distinct phenotype, with extended lifespan, increased surface expression of ICAM‐1 and CD11b, concomitant with increased TGF‐beta. Overall, the expansion of functionally compromised neutrophils during aging could contribute to the increased susceptibility to infection observed in the elderly.